Exceptional capacitance enhancement of a non-conducting COF through potential-driven chemical modulation by redox electrolyte - Kushwaha, Rinku; Haldar, Sattwick; Shekhar, Pragalbh; Krishnan, Akshara; Saha, Jayeeta; Hui, Pramiti; Vinod, Chathakudath Prabhakaran; Subramaniam, Chandramouli; Vaidhyanathan, Ramanathan (Advanced Energy Materials, 2021)
Capacitors are the most practical high-storage and rapid charge-release devices. The number of ions stored per unit area and their interaction strength with the electrode dictates capacitor-performance. Microporous materials provide a high storage surface and optimal interactions. Adsorbing electron-rich and easily polarizable molecules into microporous electrodes is expected to boost Faradaic pseudo-activity. If such electrode-electrolyte interactions can be made as a potential-driven reversible process, the resulting capacitors would be adaptable and device-friendly. A composite covalent organic framework (COF)-carbon electrode with redox-active KI is combined in an H2SO4 electrolyte for the first time. This composite electrode benefits from the redox-functionality of COF and electronic conductivity of carbon, leading to superior capacitative activity. Operando spectro-electrochemical measurements reveal the existence of multiple polyiodide species, although the I-3(-) is the predominantly electroactive species adsorbing on the microporous triazine-phenol COF electrode. A systematic fabrication of the flexible solid-state devices using the COF-redox-electrolyte reveals a high areal capacitance of 270 +/- 11 mF cm(-2) and gravimetric capacitance of 57 +/- 8 F g(-1). The inclusion of KI in H2SO4 (electrolyte) yields an approximately eight-fold enhancement in solid-state gravimetric specific capacitance. The imine-COF retains 89% of its capacity even after 10 000 cycles.
Keywords: covalent organic frameworks; polyiodide; redox electrolytes; solid‐ state capacitors; Supercapacitors

Made to measure squaramide COF cathode for zinc dual-ion battery with enriched storage via redox electrolyte - Kushwaha, Rinku; Jain, Chitvan; Shekhar, Pragalbh; Rase, Deepak; Illathvalappil, Rajith; Mekan, Deep; Camellus, Augastus; Vinod, Chathakudath Prabhakaran; Vaidhyanathan, Ramanathan (Advanced Energy Materials, 2023)
Aqueous rechargeable batteries are promising grid-scale energy storage devices because of their affordability, operational safety, and environmental benignity. Among these, Zn-ion batteries (ZIBs) have unfolded new horizons. Designing superior cathodes for ZIBs is crucial. Covalent organic frameworks (COFs) can be made redox active with a high storage surface. Here, for the first time, a chelating COF with redox-active ZnI2 in a ZnSO4(aq) electrolyte is combined. Including iodide harvests an approximately threefold enhancement in capacity from 208 to 690 mAh g(-1) at 1.5 A g(-1), the highest among all the COF-derived ZIBs. Remarkably, a charge-discharge curve at 1.3 V exhibits very limited dropout voltage and super-flat platform, with a remarkable capacity of 600 mAh g(-1) at 5 A g(-1) stable up to 6000 cycles, confirming that the polyiodide generation and storage are sustainable. The COF's dual-ion storage (Zn2+ and polyidode) delivers a ZIB with the highest energy density. Spectro-electrochemical measurements coupled with X-ray photoelectron spectroscopy unambiguously unveil the existence of multiple polyiodide species, with I-3(-) and IO3- ions as the prominent species. The latter gets reduced at the COF electrode under an applied potential, leaving I-3(-) as the major species stored on the COF. The prospect of COF-polyiodide((aq)) is a windfall for metal-ion batteries.
Keywords: covalent organic frameworks; flexible batteries; polyiodide; redox electrolytes; Zn ion batteries